Effect of concomitant Renal DeNervation and cardiac ablation on Atrial Fibrillation recurrence – RDN+AF study. (1st December 2022) - Kirstein, Bettina; Tomala, Jakub; Mayer, Julia; Ulbrich, Stefan; Wagner, Michael; Pu, Liying; Piorkowski, Judith; Hankel, Anastasia; Huo, Yan; Gaspar, Thomas; Richter, Utz; Hindricks, Gerhard; et al.
Abstract: Background: Renal denervation (RDN) can reduce cardiac sympathetic activity maintained by arterial hypertension (aHT). Its potential antiarrhythmic effect on rhythm outcome in patients with multi‐drug resistant aHT undergoing catheter ablation for atrial fibrillation (AF) is unclear. Methods: The RDN+AF study was a prospective, randomized, two‐center trial. Patients with paroxysmal or persistent AF and uncontrolled aHT (mean systolic 24‐h ambulatory BP > 135 mmHg) despite taking at least three antihypertensive drugs were enrolled. Patients were 1:2 randomized to either RDN+AF ablation or AF‐only ablation. Primary endpoint was freedom from any AF episode > 2 min at 12 months assessed by implantable loop recorder (ILR) or 7d‐holter electrocardiogram. Secondary endpoints included rhythm outcome at 24 months, blood pressure control, periprocedural complications, and renovascular safety. Results: The study randomized 61 patients (mean age 65 ± 9 years, 53% men). At 12 months, RDN+AF patients tended to have a greater decrease in ambulatory BPs but did not reach statistical significance. No differences in rhythm outcome were observed. Freedom from AF recurrence in the RDN+AF and AF‐only group measured 61% versus 53% p  = .622 at 12 months and 39% versus 47% p  = .927 at 24 months, respectively. Periprocedural complications occurred in 9/61 patients (15%). No patient died. Conclusion: Among patients with multidrug‐resistant aHT and paroxysmal or persistent AF, concomitant RDN+AF ablation was not associated with better blood pressure control or rhythm outcome in comparison to AF‐only ablation and medical therapy.